Crecimiento y reproducción de Strombus galeatus (Gastropoda: Strombidae) en el Pacífico de Costa Rica - Arroyo Mora, Daisy (Revista de Biología Tropical, 1998)
Strombus galeatus is a gastropod distributed from the Gulf of California in Mexico to the Galapagos Islands in Ecuador. and as other strombid species. in the costarican coast is a resource of high overfishing with no governmental control or regulations and scarce biological information about the species. Biological studies on this conch natural populations from managed and unmanaged areas were conducted during a four year period (November 1993 to December 1997). Results showed that this conch is found in sandy-gravel bottoms and roost of them found in less than 15 meter deep areas. Shell growth is first done in length and lip formation and afterwards on lip thickness: shell morphology was found different in juvenile and adult stages. The shell represented 8O% of total fresh weight, and presented an external brownish and white colors with some spots inside it. This dioecious species, performed a special reproductive behavior: the female genital groove appeared thickned, males seek for females, and conchs used to form groups of more than two individuals (from which one used to be a female); mating is presume d and the female lays an egg mass from which the veliger larvae appears after 3 to S days. It is believed that their most important diet is macroalgae. No predation was observed upon the conchs during surveys; no shell damage was observed in adults and little in juveniles: few adult conchs were observed with scars in the in foot and other structures. This species seems to have a high regeneration potential in juvenile and adult stages. A parasitic isopod was found attached to the upper right side of the foot in 10 of thc 627 conchs observed.